2020
DOI: 10.1111/jphp.13249
|View full text |Cite
|
Sign up to set email alerts
|

1H NMR metabolomic profiling elucidated attenuation of neurometabolic alterations by lercanidipine in MCAo model in rats

Abstract: Objectives Stroke is a leading cause of death and disability worldwide with limited therapeutic interventions. The current study explored proton nuclear magnetic resonance spectroscopy ( 1 H NMR)-based metabolomic approach to elucidate the effect of lercanidipine on neurometabolic alterations in transient model of ischaemic stroke in rats. Methods In the present investigation, male Wistar rats were subjected to middle cerebral artery occlusion (MCAo) for 2 h followed by reperfusion using intraluminal filament … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 39 publications
1
8
0
Order By: Relevance
“…Glutamine was proved possessing anti-inflammatory and antioxidant effects [ 31 ]. In this experiment, glutamine was significantly downregulated in MCAO rats, implied that glutamate metabolism was related to the occurrence of IS, which was also consistent with previous studies [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Glutamine was proved possessing anti-inflammatory and antioxidant effects [ 31 ]. In this experiment, glutamine was significantly downregulated in MCAO rats, implied that glutamate metabolism was related to the occurrence of IS, which was also consistent with previous studies [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Stroke drug treatments were characterized before by reduction of oxidative stress, lowering inflammation, and recovering energy metabolism. 67 , 68 Positive metabolite alterations after drug treatment in stroke models have been reported for glucose, lactate, ATP, and glutathione. 69 , 70 Other metabolites such as NAA have a complex interpretation.…”
Section: Discussionmentioning
confidence: 99%
“…When cerebral infarction occurred, energy metabolism disturbance appeared in the whole brain, resulting in the interruption of mitochondrial metabolism and the reduction of ATP production, which led to the production of lactic acid through anaerobic degradation of glucose. Meanwhile, creatine phosphate, another way of energy storage, was also decomposed into creatine for energy supply [ 42 ]. Once severe cerebral ischemia occurred, the death of neurons and decrease in glucose metabolism appeared one after another, which indicated that energy metabolism disorder was the root cause of cerebral IR injury.…”
Section: Discussionmentioning
confidence: 99%